Нормы русского литературного языка: учебное пособие - Константинова Л. А.; Ефремова Л. В.; Захарова Н. Н.; Малткова Т. Д.; Ненилина Н. А.; Сердюкова Н. А. (Москва, Флинта, 2010)
Авт. указаны на обороте тит.